Transcriptome analysis of two radiated Cycas species and the subsequent species delimitation of the Cycas taiwaniana complex - Xin‐Hui Wang; Wei Wu; Shu‐Guang Jian (Applications in Plant Sciences, 2019)
Premise Cycas is an important gymnosperm genus, and the most diverse of all cycad genera. The C. taiwaniana complex of species are morphologically similar and difficult to distinguish due to a lack of genomic resources. Methods We characterized the transcriptomes of two closely related and endangered Cycas species endemic to Hainan, China: C. hainanensis and C. changjiangensis. Three single‐copy nuclear genes in the C. taiwaniana complex were sequenced based on these transcriptomes, enabling us to evaluate the species boundaries using the multispecies coalescent method implemented in the Bayesian Phylogenetics and Phylogeography program. Results We obtained 68,184 and 81,561 unigenes for C. changjiangensis and C. hainanensis, respectively. We identified six positively selected genes that are mainly involved in stimulus responses, suggesting that environmental adaptation may have played an important role in the relatively recent divergence of these species. The similar KS distribution peaks at 1.0 observed for the paralogs in the two species indicate a common whole‐genome duplication event. Our species delimitation analysis indicated that the C. taiwaniana complex consists of three distinct species, which correspond to the previously reported morphological differences. Discussion Our study provides valuable genetic resources for Cycas species and guidance for the taxonomic treatment of the C. taiwaniana complex, as well as new insights into evolution of species within Cycas.